2006
DOI: 10.2337/db06-0484
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Immune Rejection in Transplanted Pancreatic Islets

Abstract: 1As islet transplantation becomes an acceptable clinical modality for restoring normoglycemia in type 1 diabetic patients, there is a crucial need for noninvasive assessment of the fate of the grafts. In spite of the success of the Edmonton Protocol, a significant graft loss occurs due to immunological and nonimmunological events immediately after transplantation. Allogeneic rejection in graft recipients is one of the major reasons for islet death and graft failure. Therefore, monitoring the islet rejection us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
170
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(195 citation statements)
references
References 42 publications
(42 reference statements)
19
170
3
Order By: Relevance
“…In the ferumoxide and in no other place. It should finally be mentioned that non-clinical grade MR scanners, with high magnetic fields (1, 11,12,18). The only pilot study performed on iron nanoparticles (17) released by dead islets are too small in size to individually disturb the MRI signal.…”
Section: Islet Function and Viability Assessmentmentioning
confidence: 99%
“…In the ferumoxide and in no other place. It should finally be mentioned that non-clinical grade MR scanners, with high magnetic fields (1, 11,12,18). The only pilot study performed on iron nanoparticles (17) released by dead islets are too small in size to individually disturb the MRI signal.…”
Section: Islet Function and Viability Assessmentmentioning
confidence: 99%
“…Superparamagnetic iron-oxide (SPIO) nanoparticle contrast agents have been used to track autoreactive T-cell migration (10 -12). In the NOD mouse, islet transplantation and pancreatic inflammation have been visualized in vivo using SPIO agents (13)(14)(15).…”
mentioning
confidence: 99%
“…But in the same situation, lesions of grafted animals were seen as dark hypointense areas. Compared to control rats, the lesions gathering by MSCs in grafted animals become considerably smaller, which suggested a positive effect of the MSCs on lesion repair [55].Moreover, several successful applications of MR tracking can be found in other organs, such as heart [56], liver [57], kidney [58] and pancreatic islets [59]. It is reported that bronchioalveolar stem cells (BASCs) were successfully isolated from the murine lung using magnetic nanoparticle-based surface-enhanced Raman spectroscopic dots (M-SERS Dots) [60].…”
Section: Figure1mentioning
confidence: 99%